PERBANDINGAN MODEL PEMBELAJARAN MURDER DAN AIR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SD NEGERI 153073 ANGGOLI I - Indah Simamora (Universitas Negeri Medan, 2022)
The Comparison of Learning Models MURDER and AIR on Mathematics Learning Outcomes of Students at SD Negeri 153073 Anggoli I. The purpose of this study was to determine the differences in mathematics learning outcomes for students at SD Negeri 153073 Anggoli I using the MURDER model with the AIR model. The population in this study were students of SD Negeri 153073 Anggoli I, with a sample of 13 students in grade II-A SD and 13 students in class II-B. The data collection technique was carried out by giving a written technical test and in the form of a description of 10 questions in the form of a pretest and posttest with multiplication and division material. The stages of the research method are normality test, homogeneity test, hypothesis testing. Then analyze the data used in this study using the two sample t-test formula. The mathematics learning outcomes of class II students at SD Negeri 153073 Anggoli I before the application of the MURDER learning model were in the medium category with an average number of 66.92 while after the application of the learning outcomes of students increased with an average number of 83.46. The mathematics learning outcomes of second grade students at SD Negeri 153073 Anggoli I before the implementation of the AIR learning model were in the medium category with an average number of 68.46 while after the application of the students' learning outcomes increased with an average number of 86.92. In testing the hypothesis using the t-test, namely the independent sample t-test, where the data being tested is the data from the posttest results of the two groups. Based on the calculation results of SPSS 16.0, Sign (2 tailed) = 0.003 which means < (0.05 or 5%), then H1 is accepted which means that there is a significant difference between the mathematics learning outcomes of second grade students at SD Negeri 153073 Anggoli I taught through MURDER and AIR learning models.